Alkali‐Metal‐Mediated Frameworks Based on Bis(2, 6‐pyridinedicarboxylate)cobalt(II) Species. Issue 31 (24th August 2017) - Mai, Hien Duy; Lee, Inme; Lee, Sangdon; Yoo, Hyojong
Abstract : Metal–organic frameworks (MOFs) with compositional multiplicity show unique topologies as well as enhanced chemical and physical properties. The construction of mixed‐metal frameworks containing more than one type of metal element can provide further structural versatility and diversity. The combination of transition‐ and alkali‐metal elements in a framework can result in interesting materials with substantial advantages. Herein, we report a synthetic strategy for the mixed transition‐ and alkali‐metal frameworks [Na2 Co(PDA)2 ] (1, PDA = 2, 6‐pyridinedicarboxylate) and [K2 Co(PDA)2 ] (2 ). The solid‐state structures of these frameworks show that two PDA ligands chelate to a cobalt ion to form a Co(PDA)2 2– species, which in turn undergoes further assembly mediated by alkali‐metal cations (Na + or K + ) to give mixed‐metal framework structures. The {[KCo(PDA)2 ] – · [NH2 (CH3 )2 ] + } framework (3 ) is also prepared by a change in stoichiometry. The multiple coordination of alkali metal atoms to the carboxylate oxygen atoms of the PDA ligands of the Co(PDA)2 2– species generates unique three‐dimensional architectures. As2 and3 react with NaOH, the coordinated K + exchanges readily with Na + in aqueous solution, and finally1 crystallizes. The strong ionic character and small size of Na + account for the facile transformations of2 and3 . Temperature‐dependent magnetization studies reveal that1 exhibits distinct magnetic susceptibility relative to those of2 and3 . Abstract : Three different mixed transition‐ and alkali‐metal frameworks resulting from the coordinative assembly of basic Co(PDA)2 2– (PDA = 2, 6‐pyridinedicarboxylate) units through the mediation of alkali‐metal ions (Na + and K + ) were successfully synthesized and thoroughly characterized.